Integrating environment into agriculture and forestry : progress and prospects in Eastern Europe and Central Asia - Sutton, William R., 1967- (World Bank e-Library., 2008)
The countries of Eastern Europe and Central Asia urgently need to accelerate the integration of environmental concerns into their agricultural and forestry sectors. Policies and laws promoting integration have undoubtedly improved, but implementation is lagging, particularly in the east and in agriculture. Integrating Environment into Agriculture and Forestry raises awareness of the pressing need to step up progress on implementation. Failure to integrate environment into agriculture and forestry will have major economic and human health implications, eg. soil salinity in Uzbekistan is estimat.